El tratamiento con glucocorticoides en pacientes con síndrome de dificultad respiratoria aguda. Una revisión sistemática de la literatura y metaanálisis (2013)
ABSTRACT: The Acute Respiratory Distress Syndrome (ARDS) is a lung inflammation secondary to primary or extrinsic pulmonary pathology. It is a common disease in the intensive care unit and its mortality rate is high. Objectives: To determine the efficacy and safety of corticosteroids in patients with ARDS older than 18 years, in terms of mortality, mechanical ventilationfree days, and safety in regard to nosocomial infections, health-care related pneumonia, neuromiopathy, and gastrointestinal bleeding. Search methods: A systematic search of electronic and manual literature was done, without restriction of language, of controlled clinical trials involving adults with ARDS, randomized to placebo vs. steroids, and that measured the outcomes described. Results: Seven clinical trials were found showing a decrease in hospital mortality (OR 0.56 [0.38-0.81], 3.5 more days free from mechanical ventilation, a decrease in nosocomial infections and in hospitalacquired pneumonia. There were no differences in the presentation of steroid-associated neuromiopathy. There was a non-significant tendency to increase in bleeding from the digestive tract. Conclusion: Low-dose steroids seem to have a beneficial effect on mortality and ventilator-free days in adult patients with ARDS with no increase in adverse effects.